2009
DOI: 10.1523/jneurosci.4195-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Reduction of PrPCLevel and Glycosylation in Peripheral Nerves following PrP Knock-Out from Schwann Cells Does Not Prevent Transmissible Spongiform Encephalopathy Neuroinvasion

Abstract: Expression of the prion protein (PrP C ) is a requirement for host susceptibility to the transmissible spongiform encephalopathies (TSEs) and thought to be necessary for the replication and transport of the infectious agent. The mechanism of TSE neuroinvasion is not fully understood, although the routing of infection has been mapped through the peripheral nervous system (PNS) and Schwann cells have been implicated as a potential conduit for transport of the TSE infectious agent. To address whether Schwann cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In contrast, acute conversion (not sustained propagation) was repeatedly observed in Rov cultures expressing PrP lacking a GPI anchor, mostly consisting of aglycosylated species, corroborating a recent study on cells that expressed mouse anchorless PrP (36). Various lines of evidence in vivo and in vitro tend to suggest that a glycosylation defect does not necessarily impair, or could even ease, PrP conversion (7,14,30,39,47,54,62). Taken together, these observations lend support to the view that the inability of aglycosylated mutants that satisfied various cell sorting quality controls to convert into PrP Sc might involve conformational dynamics of the mutant molecules, in turn affecting the efficiency of conversion process.…”
Section: Glycosylation and Prpsupporting
confidence: 80%
“…In contrast, acute conversion (not sustained propagation) was repeatedly observed in Rov cultures expressing PrP lacking a GPI anchor, mostly consisting of aglycosylated species, corroborating a recent study on cells that expressed mouse anchorless PrP (36). Various lines of evidence in vivo and in vitro tend to suggest that a glycosylation defect does not necessarily impair, or could even ease, PrP conversion (7,14,30,39,47,54,62). Taken together, these observations lend support to the view that the inability of aglycosylated mutants that satisfied various cell sorting quality controls to convert into PrP Sc might involve conformational dynamics of the mutant molecules, in turn affecting the efficiency of conversion process.…”
Section: Glycosylation and Prpsupporting
confidence: 80%
“…Importantly, Schwann cells and oligodendrocytes are highly prone to undergo ER stress as demonstrated in many different disease models due to their high demand for protein and lipid synthesis [ 2 , 69 ]. Since the PrP promoter is also active in Schwann cells [ 70 , 71 ], we propose that ERp57 may have a relevant activity in sustaining glial proteostasis as a central component of the CNX-CRT cycle. In this context, ERp57 may contribute to maintain myelin structure or to reduce stress levels in Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
“…As ME7 prions are lymphoinvasive, we examined the reasons for impaired replication and found very little if any PrP C expression in the spleen tissue of the uninfected or infected animals by immunoblot (data not shown). Incidentally, this impaired replication in the spleen is likely to have minimized haematogenous, PNS-independent prion spread to the CNS (Aucouturier et al, 2001), at variance with Bradford et al (2009). Taken together, these results argue against a major role of MSC-PrP C in prion spreading through the PNS.…”
Section: Inoculation Route Volume Inoculated* (Ml)mentioning
confidence: 95%
“…The presence of PrP Sc deposits in Schwann cells ensheathing axons from scrapie-infected sheep and mice peripheral nerves and the sustained prion replication observable in immortalized cultured Schwann-like cells experimentally infected with scrapie prions (Archer et al , 2004; Follet et al , 2002) suggested a possible role for this cell type. Transgenic mice with reduced PrP C expression in Schwann cells did not show any deceleration in the transfer of orally or intraperitoneally injected prions to the CNS (Bradford et al , 2009). These routes of prion exposure may not be optimal if the assumption that the myelin protein zero (P 0 ) promoter used in this study is active in both myelinating (MSCs) and non-myelinating Schwann cells (NMSCs) does not hold true.…”
Section: Full Textmentioning
confidence: 99%